Penerapan Nilai Etik, Norma, dan Disiplin Kesehatan dalam Praktik Pelayanan Kesehatan dengan Penyelesaian Sengketa Etik - Maryanto, Maryanto; Triadi, Irwan (Indonesian Journal Publisher, 2025)
This study aims to analyze the application of ethical values, norms, and professional discipline in healthcare practice, with particular emphasis on ethical dispute resolution mechanisms. Using a qualitative approach, this research combines normative legal analysis with case studies by reviewing laws and regulations, professional codes of ethics, guidelines, and documented cases of ethical disputes resolved through mediation and ethics committees. The study highlights the central role of ethical principles such as respect for patient autonomy, beneficence, non-maleficence, and justice in ensuring the protection of patient rights and maintaining the integrity of healthcare professionals. The findings reveal that the healthcare sector often faces complex ethical dilemmas arising from conflicts of interest, resource limitations, and professional accountability. Non-litigation mechanisms, particularly mediation reinforced by Article 310 of Law Number 17 of 2023 on Health, have proven effective in resolving conflicts fairly, transparently, and constructively. These mechanisms not only provide immediate solutions but also contribute to rebuilding trust between healthcare providers and patients while promoting restorative justice. The study concludes that integrating ethical principles with effective dispute resolution and fostering an institutional culture of ethics are crucial to strengthening professionalism, accountability, and public trust. Continuous ethical education, leadership commitment, and institutional support are key to building a sustainable healthcare system oriented toward patient welfare and social justice.